2017
DOI: 10.1002/ajhb.23015
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of postcranial indices, ratios, and body mass versus eco‐geographical variables of prehistoric Jomon, Yayoi agriculturalists, and Kumejima Islanders of Japan

Abstract: The complex interaction of evolutionary forces and development/nutritional constraints are implicated in the mismatch of limb and body proportions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…In regard to the Yayoi people, their limb and body proportions are similar to those in modern high-latitude populations in cold climates (Seguchi et al, 2017;Tahara & Kaifu, 2015;Temple et al, 2008). A previous study (Seguchi et al, 2017) proposed several possible evolutionary models to explain this result in the Jomon people: (a) the Jomon people have retained an ancestral physique associated with the climate; (b) micro-evolutionary adaptation induced by climatic change occurred during the Jomon period; and (c) the nutritional status and specific physical activities of the Jomon people affected their growth and development. Although the cause of this remains unknown, thermoregulatory adaptation would have differed between the Jomon and Yayoi peoples.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In regard to the Yayoi people, their limb and body proportions are similar to those in modern high-latitude populations in cold climates (Seguchi et al, 2017;Tahara & Kaifu, 2015;Temple et al, 2008). A previous study (Seguchi et al, 2017) proposed several possible evolutionary models to explain this result in the Jomon people: (a) the Jomon people have retained an ancestral physique associated with the climate; (b) micro-evolutionary adaptation induced by climatic change occurred during the Jomon period; and (c) the nutritional status and specific physical activities of the Jomon people affected their growth and development. Although the cause of this remains unknown, thermoregulatory adaptation would have differed between the Jomon and Yayoi peoples.…”
Section: Discussionmentioning
confidence: 73%
“…Another study reported finding a relationship between the limb and body proportions of the Jomon people. While the body proportions of the Jomon people display “wide” body breadths, which are adaptations associated with colder climates, their limb proportions are similar to those in people from tropical climates (Seguchi, Conrad, Yonemoto, & Takamuku, ; Tahara & Kaifu, ; Temple, Auerbach, Nakatsukasa, Sciulli, & Larsen, ). In regard to the Yayoi people, their limb and body proportions are similar to those in modern high‐latitude populations in cold climates (Seguchi et al, ; Tahara & Kaifu, ; Temple et al, ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Jantz & Devlin, 2016; Jantz & Meadows Jantz, 2017; Meadows & Jantz, 1995), human variation (e.g. Auerbach, 2012; Livshits et al, 2002; Seguchi et al, 2017; Tilkens et al, 2007), and growth and development (e.g. Bareggi et al, 1996; Frelat & Mitteroecker, 2011; Temple et al, 2011; Waxenbaum et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the 'standard' template itself varies among ancestral lineages, populations and species because of the evolutionary history of each (e.g. [25][26][27]). The biomedical engineering world has responded to this with the use of patient-specific models because, in patients, a direct relationship exists between a particular morphology (i.e.…”
Section: Introductionmentioning
confidence: 99%